General Equilibrium Effects of Land Market Restrictions on Labor Market : Evidence from Wages in Sri Lanka - Emran, M. Shahe (2012)
Taking advantage of a historical quasi-experiment in Sri Lanka, this paper provides evidence on the effects of land market restrictions on wages and its spatial pattern. The empirical specification is derived from a general equilibrium model that predicts that the adverse effects of land market restrictions on wages will be less in remote locations. For identification, the study exploits the effects of historical malaria prevalence on the incidence of land restrictions through its effects on "crown land". During the 16th to early 20th centuries, areas severely affected by malaria were abandoned by households and the land was taken over by the government. These lands that were later distributed through resettlement programs are subject to sales, rental, and mortgage restrictions. The variations in the amount of crown land resulting from different intensity of historical malaria provide a source of exogenous variations in the incidence of land restrictions in a sub-district. The results show that land restrictions reduce wages substantially, and this effect is smaller in remote locations. A 1 percent increase in land restrictions reduces wages by about 6.6 percent at the median travel time from an urban center, and the effect becomes effectively zero after 6 hours of travel time.